2021
DOI: 10.3171/2020.10.focvid2067
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic-assisted parieto-occipital interhemispheric precuneal transtentorial approach for microsurgical resection of vermian arteriovenous malformation: operative video and technical nuances

Abstract: In this illustrative video, the authors demonstrate resection of a superior vermian arteriovenous malformation (AVM) using the endoscopic-assisted parieto-occipital interhemispheric precuneal transtentorial approach. Lateral positioning allows for gravity-assisted access to the interhemispheric fissure without retractors. The parieto-occipital trajectory is useful in patients who have a steep tentorial angle and avoids manipulation of the occipital lobe and visual cortex. In addition, the authors utilize an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…[32][33][34] Modern adjuncts including endoscopic assistance may be used to carefully inspect deep-seated cavities, and indocyanine green injection can help localize the straight sinus before cutting the tentorium-although we use Doppler ultrasound. 6,11,35,36 While we performed a large parasagittal craniotomy on our specimens for illustrative purposes and to facilitate dissection in embalmed specimens, the use of image guidance and endoscope assistance in a clinical setting allow for tailored approaches that often result in smaller craniotomies. In addition, despite the PCIT's trajectory being longer, in the lateral position, gravity allows the parietal lobe to fall away from the falx, allowing the surgeon to shorten the working distance the approach by moving the hands into the interhemispheric fissure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[32][33][34] Modern adjuncts including endoscopic assistance may be used to carefully inspect deep-seated cavities, and indocyanine green injection can help localize the straight sinus before cutting the tentorium-although we use Doppler ultrasound. 6,11,35,36 While we performed a large parasagittal craniotomy on our specimens for illustrative purposes and to facilitate dissection in embalmed specimens, the use of image guidance and endoscope assistance in a clinical setting allow for tailored approaches that often result in smaller craniotomies. In addition, despite the PCIT's trajectory being longer, in the lateral position, gravity allows the parietal lobe to fall away from the falx, allowing the surgeon to shorten the working distance the approach by moving the hands into the interhemispheric fissure.…”
Section: Discussionmentioning
confidence: 99%
“…For arteriovenous malformations, careful attention should be paid to the venous drainage. Zhao et al 6 demonstrated the use of the PCIT for a vermian arteriovenous malformation with a superior to inferior long axis with drainage superiorly. As such, the PCIT afforded the optimal trajectory and early visualization of the draining vein, which could eventually be accessed and sacrificed when the rest of the nidus had been disconnected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations